Special diets in hospitals: discrepancy between what is prescribed and what is eaten. Issue 5951 (25th January 1975) - Davies, G J; Evans, E; Stock, A; Yudkin, J
Abstract : An assessment has been made in four hospitals of the food eaten by 40 patients on special diets restricted in energy, carbohydrate, fat, protein, or sodium. The diets eaten by most patients were significantly different from those prescribed, partly because of patients' unrestricted access to food they possessed or could buy in the ward, but mainly because of the extra or alternative foods provided by ward staff. Not only may the patients, progress be prevented or hindered by excessive consumption but also the lack of progress may be interpreted as indicating that the dietary treatment has failed rather than that it has not been followed.